Militarização de colégios públicos da rede estadual de ensino de Goiás: implicações para o direito à educação pública e gratuita - Alves, Vinicius Borges [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Esta pesquisa analisou o processo de militarização de colégios públicos da rede estadual de ensino de Goiás – denominados de Colégio da Polícia Militar de Goiás (CPMG). São escolas públicas regulares que tiveram a gestão escolar civil transferida para a gestão da polícia militar de Goiás após 2013. Além da substituição do diretor por um oficial da Polícia Militar nesses colégios é criada a Associação de Pais e Mestres com a função de administrar os recursos oriundos da contribuição voluntária mensal. É implantada uma estrutura organizacional de policiais militares distribuídos nos seguintes setores técnico-pedagógicos: divisão de ensino, administrativa, disciplinar e de finanças, regulamentados pelo Regimento Interno dos CPMG, não previstos na rede regular de ensino de Goiás. Diante disto, este estudo teve como objetivo identificar e analisar as implicações do processo de militarização na garantia do direito à educação pública. A pesquisa de abordagem qualitativa e descritiva foi desenvolvida utilizando-se dos seguintes procedimentos metodológicos: pesquisa bibliográfica e documental, pesquisa de campo por meio de observação e entrevistas semiestruturadas. Os resultados da pesquisa indicam que os CPMG podem ser considerados obstáculo ao direito à educação pública em razão das seguintes especificidades: cobrança de mensalidade denominadas “contribuição voluntária” administrada pela Associação de Pais e Mestres (ASPM); processo seletivo por meio de sorteio para acesso; critérios de desempenho e disciplina para permanência; substituição da gestão escolar eleita pela comunidade pela gestão militar.

This research analyzed the process of militarization of public schools in the state education system of Goiás – called Colégio da Polícia Militar de Goiás (CPMG). They are regular public schools that had the civil school management transferred to the management of the military police of Goiás after 2013. In addition to the replacement of the director by an officer of the Military Police, these schools create the Association of Parents and Teachers, which is responsible for managing the resources arising from the monthly voluntary contribution. An organizational structure of military police officers distributed in the following technical-pedagogical sectors is implemented: teaching division, administrative division, disciplinary division and finance division, regulated by the Internal Regulation of the CPMG, which are not provided for in the regular teaching network of Goiás. Given this, this study aimed to identify and analyze the implications of the militarization process in guaranteeing the right to public education. The qualitative and descriptive research was developed using the following methodological procedures: bibliographic and documentary research, field research through observation and semi-structured interviews. The survey results indicate that the CPMGs can be considered as an obstacle to the right to public education, due to the following specificities: collection of a monthly fee called "voluntary contribution" administered by the Association of Parents and Teachers (ASPM); selection process through drawing lots for access; performance criteria and discipline for permanence; replacement of school management elected by the community by military management.
Militarization of public schools in the state education network of Goiás: implications for the right to public and free education
Keywords: Direito à educação; Colégio militar; Gestão militar; Militarização; Right to education; Militar school; Military management; Militarization